Mykytka O. “Essays on the history of Ukrainian translation” by M. Moskalenko as an exemplary work in the field of translation studies - Mykytka O. (Philological Treatises, 2020)
This article deals with the series of articles on the history of translation, published in journal “Vsesvit” in 1993 and 2006. The article analyses scholarly and educational tonality of the “Essays”, concentrates on the key focal points of the articles, substantiates the importance and unprecedented significance of this work in the framework of Ukrainian culture.